Axillary Digital Thermometers uplifted a multidrug‐susceptible Candidaauris outbreak among COVID‐19 patients in Brazil. Issue 9 (7th June 2021) - Nobrega de Almeida, João; Brandão, Igor B.; Francisco, Elaine C.; de Almeida, Silvio Luis R.; de Oliveira Dias, Patrícia; Pereira, Felicidade M.; Santos Ferreira, Fábio; de Andrade, Thaisse Souza; de Miranda Costa, Magda M.; de Souza Jordão, Regiane T.; Meis, Jacques F.; Colombo, Arnaldo L.; et al.
Abstract: Objectives: To describe the first outbreak of Candida auris in Brazil, including epidemiological, clinical and microbiological data. Methods: After the first Candida auris ‐colonised patient was diagnosed in a COVID‐19 ICU at a hospital in Salvador, Brazil, a multidisciplinary team conducted a local C . auris prevalence investigation. Screening cultures for C . auris were collected from patients, healthcare workers and inanimate surfaces. Risk factors for C . auris colonisation were evaluated, and the fungemia episodes that occurred after the investigation were also analysed and described. Antifungal susceptibility of the C . auris isolates was determined, and they were genotyped with microsatellite analysis. Results: Among body swabs collected from 47 patients, eight ( n  = 8/47, 17%) samples from the axillae were positive for C . auris . Among samples collected from inanimate surfaces, digital thermometers had the highest rate of positive cultures ( n  = 8/47, 17%). Antifungal susceptibility testing showed MICs of 0.5 to 1 mg/L for AMB, 0.03 to 0.06 mg/L for voriconazole, 2 to 4 mg/L for fluconazole and 0.03 to 0.06 mg/L for anidulafungin. Microsatellite analysis revealed that all C . auris isolates belong to the South Asian clade (Clade I) and had different genotypes. In multivariate analysis, having a colonised digital thermometer was the only independent risk factor associated with C . auris colonisation. Three episodes of C . auris fungemia occurred after the investigation, with 30‐day attributable mortality of 33.3%. Conclusions: Emergence of C . auris in Salvador, Brazil, may be related to local C . auris clade I closely related genotypes. Contaminated axillary monitoring thermometers may facilitate the dissemination of C . auris reinforcing the concept that these reusable devices should be carefully cleaned with an effective disinfectant or replaced by other temperature monitoring methods.